Meningkatkan Aktivitas, Motivasi, dan Hasil Belajar Muatan Matematika Dengan Model Peta di Sekolah Dasar - Nur Nabiilah; Fathul Jannah (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
The problems found in this study are the low activity, motivation, and learning outcomes of students in mathematics content. This is because learning is one way, learning is less meaningful, and learning is less interesting. The application of the PETA model to mathematical content is a strategy used to overcome this problem. This study aims to describe the activities of educators, analyze the increase in student activity, motivation and student learning outcomes. This study used classroom action research which was carried out during three meetings. The research subjects were 30 students in class V at SDN Telaga Biru 6 Banjarmasin. The type of data taken is qualitative data obtained from observing the activities of educators, students, and motivational questionnaires. Quantitative data were obtained through group and individual written tests. The indicator of success to be achieved is ≥80% of all students. Based on the results of research that has been carried out using the MAP model, it is able to increase student activity, motivation, and learning outcomes.